Efektifitas Terapi Relaksasi Benson Untuk Menurunkan Kecemasan Pada Mahasiswa Peserta Uji Kompetensi Di Stikes Bala Keselamatan Palu - Ni Luh Emilia; Juliana Neng Sarman; Nova Natalia Beba; Ida Yanriatuti; Yulian Heiwer Matongka; Merli Novita (PT.Mantaya Idea Batara, 2022)
The implementation of the competency test becomes a particular concern due to the result if the examinee do not pass the test, as the result the diploma Nursing students will not be able to follow the graduation and will not be registered to become nurse candidates in Indonesia, this causes a phenomenon of feeling worry, fear, tension, anxiety and pressure on them. The purpose of this study was to know the effectiveness of Benson’s relaxation therapy on anxiety to the students who participated the competency test in Stikes Bala Keselamatan Palu. This research method used quantitative research with a pre-experimental one group pre-test and post-test design with a total samples of 22 people, according to the characteristics of the respondents. The results of this study are 22 respondents with a mean value before and after the intervention is 19.2 and 7.1 with a mean difference of 12.8 (10.83-14.71), while the statistical results obtained p value <0.05 (0.0001). The conclusion is Benson relaxation therapy is effective in reducing anxiety. The participant of Competency test need to consider this Benson relaxation technique as an alternative method to reduce anxiety or psychological problems that is experienced by the examinee when facing the exam.